A case of eclampsia complicated by cerebral haemorrhage and iatrogenic hypopharyngeal oedema and haemathoma - Kutlešić, Marija; Mostić-Ilić, Tatjana; Kutlešić, Ranko (Vojnosanitetski pregled, 2017)
Introduction. Eclampsia, serious complication of preeclampsia, can further be complicated by intracranial haemorrhage. Cesarean section under general anesthesia represents an additional risk factor. Case report. We present a case of 22 years old primipara in the 38th gestational week who after a sudden occurrence of a headache, within one hour developed eclampsia. Emergent Caesarean section was undertaken; she was intubated after several attempts. Severe tongue and hypopharyngeal edema and haemathoma made the extubation impossible; she remained intubated, sedated, mechanically ventilated, on anti-oedematous, anticonvulsive, antihypertensive therapy. On the third postoperative day, tracheostomy was performed. On the sixth day, she complained of a headache and visual disturbances. Neurological examination revealed left-sided hemiparesis. Multislice computed tomography showed intracranial hemorrhage. It was not until the closure of tracheostoma (eleventh day) that her blood pressure normalized and the headache ceased. Four days later she was dismissed from the hospital with improved clinical state. Conclusion. In order to avoid sudden and unexpected, but serious complications of preeclampsia/eclampsia, we emphasize the need of searching for more subtle signs of the disease, of prompt radiologic diagnosis and aggressive blood pressure control, with a prepared strategy for difficult airway management.